Emerging developments and practices in oncology - El Naqa, Issam (IGI Global, 2018)
"This book provides an overview of hot topics and emerging technologies in the combat cancer. The book is written by experts in the field of oncology ranging from computer aided detection, nanoparticles and targeted therapy to cancer bioinformatics and its impact on society"--Provided by publisher.